(untitled) (Comprehensive Journal of Science, 2026)
This study examines the professional and organizational challenges faced by social workers in elderly care within social institutions. The descriptive-analytical method was employed to analyze the health, psychological, social, and economic factors influencing the quality of care. The study also reviews analytical theories that explain elderly behavioral patterns and guide professional intervention. Findings show a clear gap between the needs of older adults and the available resources, with limited training and weak institutional coordination negatively affecting service effectiveness. The results highlight the essential role of social workers in supporting the elderly and promoting their independence. The study recommends developing specialized training programs, improving institutional work environments, and strengthening inter-sectoral collaboration to ensure comprehensive and sustainable elderly care.